Steady-state economics - Daly, Herman E. (Colección de libros electrónicos de ULoyola, 1991)
First published in 1977, this volume caused a sensation because of Daly's radical view that'enough is best.'Today, his ideas are recognized as the key to sustainable development, and Steady-State Economics is universally acknowledged as the leading book on the economics of sustainability.